Загальний розв'язок системи рівнянь рівноваги неоднорідних за товщиною трансверсально-ізотропних пластин - Хома, І.Ю.; Прощенко, Т.М. (Доповіді НАН України, 2010)
На основi методу розкладу функцiй y ряди Фур’є за полiномами Лежандра координати товщини побудовано систему рiвнянь рiвноваги неоднорiдних за товщиною трансверсально-iзотропних пластин i викладено метод знаходження загального аналiтичного розв’язку даної системи. On the basis of the expansion of functions in Fourier series in Legendre polynomials of the thickness coordinate, a system of equations of equilibrium for transversally isotropic plates inhomogeneous in thickness is obtained, and a method of constructing the general analytic solution of this system is given.